Combining ability studies of grain Fe and Zn contents of pearl millet (Pennisetum glaucum L.) in West Africa - Gaoh, Bassirou Sani Boubacar; Gangashetty, Prakash I.; Mohammed, Riyazaddin; Ango, Issoufou Kassari; Dzidzienyo, Daniel Kwadjo; Tongoona, Pangirayi; Govindaraj, Mahalingam (Frontiers in Plant Science, 2023)
Micronutrient malnutrition is a major challenge in Africa, where half a million children die each year because of the lack of micronutrients in the food. Pearl millet is an important food and fodder crop for the people living in the semi-arid regions of West Africa. The present study was conducted to determine the stability, combining ability and gene action conditioning the high Fe and Zn content level in grain and selected agronomic traits. Hence, eight genotypes were selected based on the availability of grain Fe and Zn contents and crossed in a full diallel mating design. Progenies from an 8 × 8 diallel mating along with the parents were evaluated in an alpha lattice design with three replications in three locations for two years. The parental lines Jirani, LCIC 9702 and MORO had positive significant general combining ability (GCA) effects for grain Fe concentration, while Jirani and MORO had positive significant GCA effects for grain Zn concentration. For the specific combining ability (SCA), among the 56 hybrids evaluated, only the hybrids LCIC 9702 × Jirani and MORO × ZANGO had positive significant SCA effects for grain Fe concentration across sites, and for grain Zn concentration, the hybrids Gamoji × MORO, LCIC 9702 × Jirani, and ICMV 167006 × Jirani had positive significant SCA effects. The reciprocal effects were significant for grain Zn concentration, grain yield, flowering time, plant height, test weight and downy mildew incidence, which suggested that the choice of which a female or male parent is critical in the hybrid production when these traits are considered. Grain Fe and Zn concentration, flowering time, plant height, panicle length, panicle girth, panicle compactness and downy mildew incidence were predominantly under additive gene actions, while grain yield and test weight were predominantly under non-additive gene action. A high positive correlation was found between grain Fe concentration and grain Zn concentration, which may imply that these traits can be improved by selecting only one. The stability analysis revealed that the hybrid ICMV 167006 × Jirani was the most stable and high yielding, with a high grain Fe and Zn micronutrients.